Effect of Heat Treatment on Fracture Toughness (KIC) and Microstructure of a Fluorcanasite-Based Glass-Ceramic - Won-suck Oh, DDS, MS1 & Eleni D. Roumanas, DDS2 (Journal of Prosthodontics, 2007)
The purpose of this study was to test the hypothesis that the increase in fracture toughness of a fluorcanasite-based glass-ceramic is a linear function of crystal volume fraction.